Digital Ecologies of Heritage Language Maintenance in Immigrant Families - Hosseini, Sajedeh Sadat (Emerging Perspectives: Interdisciplinary Graduate Research in Education and Psychology, 2025)
This paper explores how immigrant families use digital technologies to support heritage language (HL) maintenance within an ecological systems perspective. Guided by Bronfenbrenner’s Ecological Systems Theory and the Family Language Policy (FLP) model, it examines how families engage with and navigate affordances for HL practices across different layers of their lives, from home routines and community interactions to digital networks and broader sociopolitical structures. Immigrant families show remarkable resilience and creativity in adapting and mobilizing these tools, but sustainable HL maintenance requires more than individual family effort; it requires systemic change through inclusive policies, equitable access, and culturally responsive digital resources.